Mechanism of Yin-Qin oral liquid for treatment of COVID-19 based on network pharmacology - Shi-Liang JI; Li-Ping HE; Dong-Kai GUO; Wei WANG; Hui CHEN; Yi-Guo JIANG; Cheng WANG (Yixue xinzhi zazhi)
Objective  To explore the potential active components and molecular mechanism of Yin-Qin oral liquid(YQOL) for treatment of pediatric coronavirus pneumonia (COVID-19).Methods With the help of TCMSP and BATMAN-TCM platform obtaining honeysuckle, scutellaria baicalensis, bupleurum, cicada slough active chemical constituents and action targets. Through UniProt, GeneCards database convert Target and gene, and then Cytoscape3.7.2 was used to construct the “active-target” networks and perform topological analysis, The core targets were analyzed by GO and KEGG functional enrichment analysis by R software.Results The network analysis indicated that 56 active ingredients affected 266 key target proteins, and the key targets involve PTGS1, GSK3β, NCOA2, ESR1, ESR2, etc. The function enrichment analysis of GO was involved in 237 biological processes(BP), 54 cell components (CC), and 65 molecular function (MF). There are 66 items enriched in KEGG pathway, involving Neuroactive ligand-receptor interaction, cancer and cAMP signaling pathway, etc. Molecular docking revealed that bupleurum, scutellaria baicalensis and honeysuckle contained more potential anti-covid-19 active ingredients, and Bupleurum saponins (A, D), baicalin and isopterin have the strongest affinity.Conclusion The active compounds in YQOL may interfere multiple pathways through antivirus, inhibition of inflammatory factors and regulation of immunity and provide a research direction for elucidation of the anti-COVID-19 pharmacological mechanism of YQOL.